An alternative space where to stay and learn. Children with scholar failure experiences building their classroom in a Community Center (Praxis Educativa, 2014)
This article is interested on the negative impact left by the scholar failure experiences and the conditions that promote the development of learning possibilities focusing on the space. In this frame, communicate the findings of a case study about a grade with alternative conditions to conventional scholar ones. Between them, they had weekly activities in a common school and they functioned daily in the classroom of a Community Center. The ways of using that space are described through the “regions” that the teacher and the children –with repeated scholar failure experiences– configured during the year. The rebuilding of this process and the analysis of the key role developed by the teacher allowed to identify as features of the organization and use of the space, the stability, the openness and the adaptation. These contributed with the children’s change from inhibited and repetitive modes of using the classroom to testing new ones, increasing their circulation and building knowledge about it. Because of this, the space is considered to constitute a third element mediator of the group relations and the action in a positive way to the developing of children’s potential.
Keywords: alternative educative answers; space; stability; openness; adaptation; mediation